Visual Function and Disability Are Associated With Focal Thickness Reduction of the Ganglion Cell-Inner Plexiform Layer in Patients With Multiple Sclerosis - Shi, Ce; Jiang, Hong; Gameiro, Giovana Rosa; Hu, Huiling; Hernandez, Jeffrey; Delgado, Silvia; Wang, Jianhua (Investigative ophthalmology & visual science, 2019)
The purpose of this study was to visualize the topographic thickness patterns of the intraretinal layers and their associations with clinical manifestations in patients with multiple sclerosis (MS). Ninety-four eyes of 47 relapsing-remitting MS patients without history of optic neuritis were imaged using optical coherence tomography and compared with 134 eyes of 67 healthy subjects. Volumetric data centered on the fovea were segmented to obtain the thickness maps of six intraretinal layers. The thickness measurements partitioned using the Early Treatment Diabetic Retinopathy Study (ETDRS) partition were correlated to the Expanded Disability State Scale (EDSS) and Sloan low contrast visual acuity (LCVA). The receiver-operating characteristics (ROC) curves were calculated to obtain the area under the ROC curves (AUCs). The ganglion cell-inner plexiform layer (GCIPL) showed horseshoe-like thickness reduction profoundly at the nasal sector. The most profound thickness reduction zone (circular area, diameter = 1 mm) was located at 2 mm in the nasal sector and 0.4 mm inferior from the fovea, named the "M zone." The thickness reduction of the M zone was -7.3 μm in MS eyes, which was the most profound alteration, compared to any ETDRS sectors. The AUC of the M zone was 0.75. The relationship between the thickness of the M zone and EDSS (r = -0.59, P < 0.001) or 2.5% LCVA (r = 0.51, P < 0.001) were ranked as the strongest relation compared to any ETDRS sectors. This is the first study, to our knowledge, to visualize focal thickness alteration of GCIPL and reveal its relationship to visual function and disability in patients with MS without history of optic neuritis.